Pengaruh Efektivitas Iklan dan Daya Tarik Iklan terhadap Brand Attitude Sarimi - Kris Muharamai Mareza; Thamrin Thamrin (Jurnal Ecogen, 2021)
This study aims to see the effectiveness of advertisements and the attractiveness of advertisements on Sarimi's brand attitude among students of Padang State University. This type of research is a causative research. The sample in this study was 96 students of Padang State University who were selected using purposive sampling method. The types of data in this study are primary data and secondary data. The data were collected by using a questionnaire technique and analyzed using multiple regression analysis methods. Testing instruments using validity and reliability tests. The prerequisite analysis tests included normality test, multicollinearity test and heteroscedasticity test. The collected data were processed with SPSS version 20.0. The results of this study indicate that the effectiveness of advertisements and the attractiveness of advertisements has a significant positive effect on Sarimi's brand attitude among students of Padang State UniversityKeywords : efektivitas iklan, daya tarik iklan, brand attitude